Jurisdição constitucional e o sistema político-representativo: uma análise do papel do Supremo Tribunal Federal para a consolidação da democracia - Oliveira, Ana Claudia Beppu dos Santos (2010)
Constitutions arose as a proper tool to establish and legitimize the government bound to the sovereign will of the people. Currently, Constitutions are also guarantors of political, social, economic, cultural and diffuse rights. The constitutional concept is founded on the idea of supremacy of the Constitution, and from this idea, results the judicial review of laws. After the middle of the twentieth century, the judicial review was expressly incorporated into various jurisdictions. There is, however, a strong democratic objection to the judicial review, under the rationale that judges are not elected by popular vote and therefore could not control rules issued by those to whom the people delegated the exercise of political power. In this debate, one can identify three positions: a more radical one, defending the judicial self restraint, and two others advocating the legitimacy of the judicial review by the judicial procedure (to preserve the integrity of the democratic process) or by substance (to ensure moral rights to individuals, aimed at the collective welfare). Despite this discussion, the possibility of judicial review is confirmed in the Brazilian legal system since the Constitution of 1891. Under the 1988 Constitution, the task of "guardian of the Constitution" rests with the Federal Supreme Court, which exercises it both by means of concentrated control or when it analyzes, in the higher instance, constitutional issues raised in the sphere of diffuse control. It is worth mentioning that STF is not far from its function of protecting the Constitution, even when it performs other roles conferred on it. From the analysis of decisions issued by Federal Supreme Court in hard cases regarding the political-representative system, this thesis aims at inquiring how the Federal Supreme Court understands its institutional role in defining political issues and to what extent the constitutional jurisdiction contributes to the maturing of the Brazilian democratic system.